The role and therapeutic effectiveness of Plantago ovata husk (psyllium husk) in the prevention and non-pharmacological treatment of gastrointestinal diseases. Part 2. Clinical use of psyllium husk in the treatment of constipation and diarrhea - Przybyszewska, Justyna; Kuźmiński, Andrzej; Przybyszewski, Michał; Popławski, Cezary (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
The results of numerous clinical studies available in the literature allow us to conclude that the fiber deserving the name of the gold standard in regulating bowel movements is the psyllium husk obtained from Plantago ovata. The physicochemical properties of psyllium, related to its ability to form a gel in an aqueous environment and its ability to retain water in this mucous-gel structure, mean that preparations containing P. ovata husk show therapeutic effects in both constipation (including occasional and chronic) and diarrhea (acute and chronic). Moreover, the results of studies and clinical experiments indicate that the use of P. ovata husk in the treatment of bowel disorders is distinguished by significantly higher efficacy compared to pharmacological preparations such as sodium docusate or loperamide. This article presents the evidence available in the recent literature on the therapeutic potential and possible mechanisms of action of Plantago ovata husk in the treatment of constipation and diarrhea.